Hybrid bio-based composites from blends of epoxy and soybean oil resins reinforced with jute woven fabrics. (20th January 2020) - Ozkur, Semih; Sezgin, Hande; Akay, Erdem; Yalcin-Enis, Ipek
Abstract: In our world, where environmental factors are taken into consideration more and more, the interest in biomaterials leaves its place to the need and this leads the researchers to search for new materials. The aim of this study is to produce an environmentally friendly, sustainable material with the use of a plant oil-based bio-resin (acrylated epoxidized soybean oil). In this context, bio-composites containing different proportions (from 0 to 100 wt%, in 10% increments) of acrylated epoxidized soybean oil (AESO) and epoxy resin are reinforced with four-ply jute woven fabric and produced by the vacuum infusion method. The bio-composites produced within the scope of the study analyzed physically (fiber weight ratio), mechanically (tensile strength, flexural strength, drop-weight impact resistance, and Charpy impact strength), instrumentally (differential scanning calorimetry and Fourier-transform infrared spectroscopy) and morphologically (scanning electron microscopy). According to the results, the tensile and flexural strength values of the composites containing more than 30 wt% AESO resin decrease due to the ductility of the structure; subsequently, composites with AESO content above 50 wt% are found to exhibit superior impact resistance. Composites with pure AESO resin absorb 7 J energy which is almost 3 times higher than pure epoxy composites. The maximum tensile strength (63 MPa) of composites are achieved for 30 wt% AESO content indicating the newly formed hydrogen bonding leading to enhanced fiber-matrix interface. The bio-composites designed and produced in the project have been a promising alternative for various end-use areas, from construction elements to the automotive sector and sports equipment, where human health and environmental elements are considered.